Time course and cytokine dependence of human T-cell lymphotropic virus type 1 T-lymphocyte transformation as revealed by a microtiter infectivity assay. - Persaud, D (1995)
Human T-cell lymphotropic virus type 1 (HTLV-1) enhances the growth of T lymphocytes, allowing the generation of T-lymphocyte cell lines. This report describes a limiting-dilution assay system which uses low input numbers of HTLV-1-producing cells for generation of T-lymphocyte cultures. The HTLV-1 transformants generated with this assay system produced high levels of HTLV-1 p24 antigen and required exogenous cytokines for maintenance. Clonal populations of CD4- or CD8-positive HTLV-1 transformants were generated with transformation efficiency rates as high as 78%. An exogenous cytokine is necessary for HTLV-1 T-lymphocyte transformation, and cytokine dependence is the most likely outcome of infection and transformation. HTLV-1 T-lymphocyte transformation can occur in the presence of cytokines other than interleukin-2 (IL-2), such as IL-4 or IL-7. IL-4- or IL-7-dependent HTLV-1 transformants underwent T-lymphocyte mitogenesis in response to their homologous cytokines but proliferated best in the presence of IL-2. Since the receptors for IL-2, IL-4, and IL-7 share the IL-2 gamma chain, this component may be the common element in the signaling pathway for HTLV-1-associated transformation.